"Saturn" remains in orbit - Chmil, V. M.; Glushechenko, E. N. (Technology and design in electronic equipment, 2013)
The article is dedicated to scientific and production enterprise "Saturn" — since its foundation up to the present day. The authors describe the determining stages of its development and its team’s scientific and technological achievements over the 45-year history of the enterprise.